Effects of Intercropping Finger Millet (Eleusine coracana) with Common Beans (Phaseolusvulgaris) on Weed Management in Finger Millet in Trans Nzoia County, Kenya - Sululu, P.; Ngode, L.; Anjichi, V. (Africa Environmental Review Journal, 2022)
Weed infestation is considered as one of the most important constraints affecting finger millet production causing significant yield losses. Weed management is a critical component of any farming system. Management of weeds is important for enhancing the production of finger millet. Recent research efforts suggested that intercropping legumes with cereals can have potential for weed suppression and may decrease the need to use herbicides. This study was aimed at evaluating theeffects of intercropping finger millet (Eleusine coracana) with common beans (Phaseolusvulgaris) on weed managementin finger millet in Trans - Nzoia County, Kenya. Field experiments were conducted on- farm at Kiminini Sub-County in Trans-Nzoia County. The treatments were laid out in a Randomized Complete Block Design (RCBD) over two seasons (2020 short rains and 2021 long rains season). The three improved finger millet varieties (Gulu- E, U-15 and P-224) and common bean variety (Rosecoco) were used. Each finger millet variety was grown in monoculture and intercropped with beans. The treatments were replicated three times giving a total of 27 plots. The plots measured 1.8m x 1.5m each and a path of 1m was used to separate one plot from the other. Parameters that were recorded during the growing season on weeds included; weed type, weed count and weed biomass. Data collected was subjected to analysis of variance (ANOVA) to determine the effects of seasons, treatments and their interaction using the mixed procedure of SAS (Institute 2012) software. The means of seasons, treatments and their interaction were compared by least significance difference at p< 0.05. The weedy treatments recorded the highest weed count and weed biomass. Finger millet-bean intercrop recorded the lowest valuesof weed count and weed biomass. The long rains season recorded significantly higher weed biomass than the short rains season. Intercropping was superior to monocropping in terms of smothering weeds. Small scale farmers in Trans-Nzoia County should be encouraged to grow finger millet varieties intercropped with common bean to assist in weed suppression and improve finger millet yield.